Equestrian Games in Turkish history - Özen, Abdullah; Devecioglu, Sebahattin; Özen, Rahşan (My University, 2012)
The horse as one of the fundamental aspects of the daily life of Turks caused formation and accumulation of a significant social and cultural values and later the emerging of the sportive activities based on the horse as a natural result. The Turks of the Middle Asia developing such skills in the horse equestrianism and archery as horse breeder and hunter shepherd to survive, showed themselves off in the books of history and generated the first forms of the horse related sportive activities in early periods. This study was carried out to put forth and analyze the equestrianism activities that have anoteworthy place in the history of the Turkish folk lore as well as to state the reasons of creating such a culture, the application methods, its functions within the society and the changes in these functions through the history and to determine the contributions of the Turkish folklore to the current application methods of the horse related games.
Keywords: History; folk culture; horses; horse riding; horse racing